Multilayer varistor and method for manufacturing multilayer varistor
Patent Information
- Application Number
- JP2022512767
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-26
- Filing Date
- 2021-07-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-07-26
AI Technical Summary
【0054】 以下に記述される図面は、縮尺どおりと解釈されてはならない。むしろ、より良好な図示のために、個々の寸法が拡大、縮小あるいは歪曲されて示されている可能性がある。
Smart Images

Figure 0007638964000003 
Figure 0007638964000004 
Figure 0007638964000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer varistor.The present invention further relates to a method for producing a multilayer varistor. [Background technology]
[0002] Multilayer varistors are used as effective protection elements against temporary overvoltages (such as ESD - "electrostatic discharge"). Rapidly developing communication technology increases the demand for protection elements to protect sensitive electronic equipment. Due to the high frequencies in signal transmission and because these protection elements are directly integrated into the circuits, the capacitance of these components must be kept as small as possible. Otherwise, failures and losses will occur inside the circuits that conduct the signals.
[0003] Reducing the capacitance of multilayer varistors poses considerable challenges. In construction, the active area (overlap area) and therefore the capacitance can be made smaller, but this reduces the leakage current and the protective effect proportionately. From a material point of view, a material with a lower dielectric constant (DK) is desirable. The material used for multilayer varistors consists of doped zinc oxide (ZnO). The DK of this ceramic is dominated by the barrier layers between the ZnO grains. The series and parallel connection of the individual barrier layers results in the capacitance, but also in the breakdown voltage of the active area. Since the breakdown voltage is predefined in the design of the component, it also results in the capacitance of the active area. The DK of the ZnO ceramic is strongly linked to the breakdown voltage and therefore cannot be used as a degree of freedom to reduce the capacitance.
[0004] In addition to the capacitance of the active volume (the ceramic between the internal electrodes), the capacitance of the varistor is also contributed by the stray capacitance of the ceramic parts outside the active volume (the covering layers and the insulating zones). As the active area in the component becomes smaller, the proportion of stray capacitance in the total capacitance increases more and more, so that structures in which the electrodes have a minimum overlap area limit the achievable effect. To effectively reduce the capacitance of the varistor, it is therefore necessary to reduce this stray capacitance as much as possible.
[0005] Various methods are known to reduce the electrical conductivity and the stray capacitance in the area outside the internal electrodes, but they are not very effective or have other drawbacks. The easiest way to achieve this is to glaze the surface of the multilayer varistor after sintering. This glass layer has the additional advantage of chemically isolating the ceramic and thereby increasing the durability of the component. The additional use of this method can therefore be effective even when other methods are used. However, since the glass layer is very thin, the effectiveness of this method is limited and the use or combination with other methods is advantageous.
[0006] In the patent application WO 2005 / 023333, instead of a protective glass layer, a coating layer containing bismuth is applied as electroplating protection, which can be sintered together with the varistor ceramic. The chemical composition of the coating layer is very different from the ZnO ceramic, which leads to unfavorable diffusion and reaction zones during sintering. The influence of the dielectric constant by the coating layer is not discussed.
[0007] US Pat. No. 5,399,433 describes a method in which the outermost region of the ceramic is chemically modified after sintering. During an additional heat treatment, lithium or sodium is diffused into the surface of the ceramic body. By doping with acceptors, the leakage current and the relative dielectric constant of the outermost layer are reduced. The capacitance of the multilayer varistor can be significantly reduced in this way. The disadvantage of this method is that this subsequent modification represents a considerable effort. Furthermore, a further heat treatment would be required to apply an additional glass layer on the outside, which is extremely difficult to implement due to the high diffusion rates of sodium and lithium.
[0008] US Pat. No. 5,399,433 describes a multilayer varistor consisting of an insulating carrier layer with a low dielectric constant, on which the actual varistor ceramic is laminated. The carrier layer itself is also produced in a layer process from a ceramic with a low dielectric constant. The disadvantage of this multilayer varistor is its laborious production, and instead of a single ceramic, two different ceramics with widely different properties are required. This can be achieved by different chemical compositions, but the result is a weak bond between the carrier layer and the varistor ceramic.
[0009] US Pat. No. 5,399,433 describes a multilayer varistor made of two chemically very different materials, which differ in ZnO grain size after the sintering process. The purpose of this construction of the multilayer varistor is to keep the current in the component away from thermomechanically weak sites, thereby increasing the pulse strength of the protection element. In that case, the influence on the capacitance of the multilayer varistor of, for example, very different chemical materials, both of which are used in the active area, is not of interest.
[0010] US Patent No. 5,399,633 describes the combination of two different ZnO ceramics to increase the pulse strength of a component. The two materials must be joined to an electrode to show any effect. Effects in the near-surface region and on capacitance are not addressed.
[0011] Thus, the known methods show obvious drawbacks or do not provide any effectiveness in reducing stray capacitance. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] German Patent No. 10026258 [Patent Document 2] Patent No. 3735151 [Patent Document 3] Japanese Patent Application Publication No. 11-003809 [Patent Document 4] DE 102018116221 A1 [Patent Document 5] DE 102017105673 Summary of the Invention [Problem to be solved by the invention]
[0013] The object of the present invention is to describe a multilayer varistor and a method for producing a multilayer varistor which solves the above mentioned problems. [Means for solving the problem]
[0014] This problem is solved by a multilayer varistor and a method for producing a multilayer varistor according to the independent claims.
[0015] According to one aspect, a multi-layer varistor is described. The multi-layer varistor comprises a ceramic body. The ceramic body comprises a plurality of layers. A number of internal electrodes are formed within the ceramic body. The internal electrodes may comprise, for example, silver, palladium, platinum, or alloys of these metals.
[0016] The ceramic body has active areas. The ceramic body further has inactive areas. An active area is to be understood as an area between different internal electrodes of different polarity, which is decisive for the current flow between said internal electrodes. In contrast, an area in the ceramic body of a multilayer varistor that does not contribute (or does not substantially contribute) to the current flow between differently contacted internal electrodes is called an inactive area.
[0017] The ceramic body has a near-surface region adjacent to the top and bottom surfaces of the multilayer varistor, respectively. The near-surface region has minimal electrical conductivity. The near-surface region is configured to be substantially electrically insulating. The near-surface region includes a coating layer and / or an insulating zone of the multilayer varistor.
[0018] The ceramic body comprises at least one first or primary ceramic material. Preferably, the multilayer varistor comprises exactly one first or primary ceramic material. The ceramic body comprises at least one second or modified ceramic material. The main component of the two ceramic materials is zinc oxide (ZnO). In particular, the two ceramic materials are based on ZnO.
[0019] The first and second ceramic materials are each composed of a monovalent element X + or in the concentration of elements having a stable oxidation state +I, where X + Li + , Na + , K + or Ag + Preferably, the monovalent element has a low diffusion constant. Preferably, the multi-layer varistor is manufactured by the method described in detail below.
[0020] The second or modified ceramic material is doped with a monovalent element. For example, the second ceramic material is doped with potassium oxide. The first or primary ceramic material may not be doped with a monovalent element. However, alternatively, the first ceramic material may be slightly doped with a monovalent element.
[0021] The dopants that differentiate the ceramic materials occur in low concentrations. By doping with a monovalent element, the electrical properties of the second / modified ceramic material are indeed significantly different from those of the first / primary ceramic material. Chemically, however, there is no significant difference between the ceramic materials. In particular, the two materials are otherwise nearly identical.
[0022] Doping with monovalent elements, even in small amounts, results in a clear reduction in the dielectric constant. Thus, the second or modified ceramic material has a lower dielectric constant than the first or primary ceramic material. This can provide a multilayer varistor with reduced stray capacitance and therefore reduced total capacitance.
[0023] According to one embodiment, the monovalent element X + The highest concentrations of monovalent elements X are present in the near-surface region. + The lowest concentration of monovalent elements is present in the active region. Thus, the concentration of monovalent elements decreases from the surface of the multilayer varistor towards the inner / active region. Correspondingly, the value of the dielectric constant increases from the surface of the multilayer varistor towards the inner region, thereby reducing the stray capacitance of the varistor. Thus, the total capacitance of the varistor is effectively reduced.
[0024] According to one embodiment, the ceramic materials differ from each other chemically by ≦1%. In other words, the ceramic materials are chemically almost identical. The two materials can therefore be processed together well. For example, layers of modified materials can be sintered together without defects. Thereby, a particularly reliable multilayer varistor is provided.
[0025] According to one embodiment, the relative dielectric constants ε of the first and second ceramic materials are r differ from each other by a factor of more than 5. Therefore, by doping only slightly with monovalent elements, the stray capacitance of a varistor can be easily and significantly reduced.
[0026] According to one embodiment, a first / primary ceramic material is arranged in the active area. A second / modified ceramic material forms an insulating coating layer of the ceramic body. In particular, the second ceramic material is arranged on the upper and lower surfaces of the multilayer varistor. Thus, the multilayer varistor has an insulating coating layer or cover with a low relative dielectric constant. Thus, the stray capacitance of the multilayer varistor is easily significantly reduced compared to conventional multilayer varistors.
[0027] According to one embodiment, the ceramic material is made of a monovalent element X + At a concentration of 50 ppm or less, + )≦5000 ppm, where Δc denotes the maximum concentration difference that can occur between the active area and the near-surface area.
[0028] In other words, the concentration of the acceptor is at most 50 ppm to 5000 ppm higher in the second ceramic material than in the first ceramic material. Preferably, the ceramic material of the multilayer varistor has a concentration of 100 ppm≦Δc(X + ) ≦ 1000 ppm.
[0029] Monovalent element X + is preferably less than 100 ppm, preferably less than 50 ppm, in the active area. The first ceramic material therefore contains very little monovalent elements, the proportion of which is due in particular to their diffusion from the second ceramic material during the manufacture of the multilayer varistor.
[0030] The monovalent elements that distinguish the two ceramic materials only have a small concentration difference (concentration gradient), so their diffusion into the active area is negligible even during sintering. Therefore, the covering layer (second or modified ceramic material) can be dimensioned with a sufficiently large thickness, which enhances the shielding effect.
[0031] According to one embodiment, the ceramic body comprises at least three ceramic materials. In particular, the ceramic body comprises a first / primary ceramic material, a second / modified ceramic material, and a third / modified ceramic material. However, the ceramic body may also comprise more than three ceramic materials. For example, the ceramic body may further comprise a fourth or modified ceramic material.
[0032] The third ceramic material is disposed between the first and second ceramic materials. The third ceramic material is disposed in the inactive areas of the multilayer varistor, particularly in the area near the surface. The third ceramic material forms an insulating zone near the surface. The three ceramic materials differ chemically by ≦1%.
[0033] The three ceramic materials differ in their concentration of monovalent elements: the first ceramic material (active area) has the lowest concentration of monovalent elements, the second ceramic material (outer insulating coating layer) has the highest concentration of monovalent elements, and the third material (insulating zone near the surface) has a concentration of monovalent elements between the concentrations of the first and second ceramic materials.
[0034] In particular, monovalent element X + The concentration of gradually decreases (concentration gradient) from the near-surface region toward the active region, thus effectively reducing local chemical differences.
[0035] According to one embodiment, the thickness of the second and / or third ceramic material is adapted to the diffusion behavior of the monovalent element. In particular, the thickness is selected such that the diffusion of acceptors into the active area is as little as possible. The thickness of the covering layer is therefore adapted to the diffusion constant of the monovalent element. In particular, the thickness decreases as the diffusion constant increases. Due to the reduced diffusion, a defined concentration gradient of the monovalent element results and, in connection with this, a defined gradient of the electrical properties, in particular of the dielectric constant, results.
[0036] The thickness of the second and third ceramic materials is adapted to the overall height of the part and its internal structure. It is considered as a design principle that the higher the proportion of the second and third ceramic materials in the inactive coating layer, the greater the effectiveness. On the other hand, this increases the risk of monovalent elements diffusing into the active area during sintering. For example, a safety distance of 100 μm can be effective. In other words, after the last printed stack, there is another 100 μm of the first ceramic material as a "diffusion buffer". However, smaller safety distances are also conceivable. Alternatively, the last printed layer may be directly followed by the second and third ceramic materials.
[0037] According to a further aspect, a method for producing a multilayer varistor is described. Preferably, the method produces a multilayer varistor as described above. All features disclosed with respect to the multilayer varistor or the method are correspondingly disclosed with respect to each other aspect and vice versa, even if the respective feature is not explicitly mentioned in the context of the respective aspect. The method comprises the following steps:
[0038] A) providing a first or primary ceramic powder for producing a first ceramic material, and A) providing at least one second or modified ceramic powder for producing a second ceramic material.
[0039] The ceramic powder substantially contains ZnO. The second ceramic powder contains a monovalent element X +For example, Li + , Na + , K + or Ag + The first ceramic powder may contain no doping of monovalent elements or may contain only a slight doping of monovalent elements. In particular, the concentration of the monovalent elements in the first ceramic powder is many times lower than the concentration of the monovalent elements in the second ceramic powder. The dopant has a small diffusion constant.
[0040] For example, there can be a doping of potassium (for example KO, KC4H5O6 or K2Co3). The latter in particular are characterized by their high melting point and high decomposition temperature, which results in little loss during sintering. Alternatively, for example Li or Na can be used as doping. Na and Li cause little or no peroxide formation in air and the melting points of the metals are very high. Thus, losses during sintering can be kept low.
[0041] The dopants appear only in low concentrations. The ceramic powder contains only monovalent elements, X + At a concentration of 50 ppm or less Δc(X + )≦5000 ppm, where Δc represents the maximum concentration difference that can occur between the active area and the near-surface area of the completed multilayer varistor.
[0042] In an alternative embodiment, a third ceramic powder can be additionally prepared to produce a third ceramic material, where the monovalent element X in the third ceramic powder is + The concentration of the monovalent element is less than in the second ceramic powder but greater than in the first ceramic powder. The third ceramic powder contains a medium concentration of the monovalent element.
[0043] B) Slurrying the ceramic powder in a solvent and rolling or forming a green sheet.
[0044] C) To form an internal electrode, a metal paste, for example, silver and / or palladium, is printed on a portion of the green sheet. Here, the monovalent element X is more abundant than the other green sheets. + The green sheet having the smallest concentration of the monovalent element is partially printed with the metal paste. In particular, the green sheet having the smallest concentration of the monovalent element is printed on the green sheet, i.e., the green sheet made from the first ceramic powder.
[0045] Additionally, metal pastes can be printed onto additional green sheets containing minimal or moderate concentrations of monovalent elements to form faradaic or shield electrodes.
[0046] D) Stacking the printed and unprinted green sheets, where the green sheets are stacked such that the second ceramic material forms the covering layer of the multilayer varistor, and where a third ceramic material is present, the green sheets are stacked such that the green sheets of the third ceramic material are disposed between the green sheets of the first and third ceramic materials.
[0047] The green sheet is particularly + The layers are stacked to form a defined concentration gradient, with the concentration decreasing from the second ceramic material (the coating layer) to the first ceramic material (the active area).
[0048] E) Laminating, decarburizing and sintering the green sheets. Preferably, the green sheets are sintered at 1100°C.
[0049] F) For electrical contacting of the multilayer varistors, the external electrodes are applied. The external electrodes can be formed as single layers (CN type) or as multilayers. In the case of three-layer external electrodes, electroplating is followed by the application of an additional Ni layer and a solderable Sn layer. Before electroplating, the components must be provided with a protective layer (glazing).
[0050] In this method, the modified ceramic materials are of particular importance. Since the modified ceramic materials are intended to be produced by the same methods as the primary ceramic materials and the various ceramic materials are intended to be processed together in stacking, lamination and sintering steps, it is important that the mechanical and thermal properties of the materials are well matched to each other. At the same time, the electrical properties must be adapted to the very different requirements.
[0051] Here, the concept of covering layers or covers with low dielectric constants is used to reduce the capacitance of the multilayer varistor. Conventional solutions either require laborious methods and / or additional process steps for their production or are not suitable for reducing the stray capacitance. The diffusion of lithium into the sintered components is a special challenge. In that case, treatment with highly concentrated lithium compounds (e.g. Li2CO3) is necessary to achieve a sufficient penetration depth, but on the other hand there is a risk that the lithium will penetrate into the active volume and thus jeopardize the functionality of the component.
[0052] On the other hand, if ceramics with a significantly different chemical composition are used as coating layers, in addition to the manufacturing effort, there is the disadvantage that the bond between the coating layer and the varistor ceramic is minimal. The mechanical properties (elastic modulus, strength, thermal expansion, etc.) are partially significantly different from each other, because a sufficient difference in the electrical properties is required. The mechanical stability of the whole component is thereby adversely affected.
[0053] These drawbacks are effectively avoided by the method and resulting multilayer varistor described above.
[0054] The drawings described below should not be construed as being to scale, rather individual dimensions may be shown enlarged, reduced or distorted for better illustration.
[0055] Components which are identical to one another or which perform the same functions are designated by the same reference numerals. [Brief description of the drawings]
[0056] [Figure 1] 1 is a cross-sectional view of a multilayer varistor according to a first embodiment. [Diagram 2] FIG. 4 is a cross-sectional view of a multilayer varistor according to another embodiment. [Diagram 3] FIG. 11 is a cross-sectional view of a multilayer varistor according to a third embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0057] Figure 1 shows a first embodiment of a multilayer varistor 1. The multilayer varistor 1 comprises a ceramic body 2. In the ceramic body 2, a number of internal electrodes 5 are formed. In Figure 1, only two internal electrodes 5 are shown. Of course, the multilayer varistor 1 can have more than two internal electrodes 5. The internal electrodes 5 comprise silver, palladium, platinum or an alloy of these metals.
[0058] In this embodiment, the internal electrodes 5 are arranged alternately and overlap in an internal region of the multilayer varistor 1. The overlapping region forms the active region 3 of the multilayer varistor 1.
[0059] The multilayer varistor 1 further comprises a near-surface region 4, which has minimal electrical conductivity. The near-surface region 4 is adjacent to the top surface 1a and the bottom surface 1b of the multilayer varistor 1, as can be seen in Figure 1. The near-surface region 4 comprises a coating layer or insulating region of the multilayer varistor 1.
[0060] In this embodiment, the multilayer varistor 1 further has two external electrodes 9. However, the multilayer varistor 1 may have more than two external electrodes 9. The external electrodes 9 are electrically connected to the internal electrodes 5 for electrical contact of the multilayer varistor 1. The external electrodes 9 are formed on the side surfaces of the multilayer varistor 1. Furthermore, the external electrodes 9 are also formed on the lower surface 1b and a part of the upper surface 1a of the multilayer varistor 1.
[0061] According to the illustrated embodiment, the outer electrode is constructed as a single layer.
[0062] Alternatively, the external electrodes 9 can be constructed as a multi-layer (not explicitly shown). Preferably, each external electrode 9 has a first or inner layer, in this case for contacting the internal electrodes 5. The first layer preferably comprises silver. Each external electrode 9 has a second or intermediate layer as a diffusion barrier. The second layer preferably comprises nickel. Each external electrode 9 has a third or outer layer, which allows soldering of the multilayer varistor 1 onto a circuit board. The third layer preferably comprises tin. In this embodiment, the varistor 1 must be provided with a protective layer (preferably glass) before electroplating. In particular, in this case, on the upper face 1a and on the lower face 1b (i.e. over the second ceramic material 7 described below) another protective layer (electroplating protection, e.g. glass) is applied (not explicitly shown). This glass layer chemically isolates the ceramic body 2 and thus increases the durability of the varistor 1.
[0063] The ceramic body 2 comprises, in the embodiment according to FIG. 1, two ceramic materials or varistor ceramics 6, 7.
[0064] A first or primary ceramic material 6 is formed in an interior region of the multilayer varistor 1. In particular, the active region 3 comprises the first ceramic material 6. A second or modified ceramic material 7 is formed in a peripheral region of the multilayer varistor 1. In particular, the second ceramic material is arranged in the near-surface region 4 and thus substantially in the non-active region. However, in addition to the second ceramic material 7, the non-active region also comprises a portion of the first ceramic material 6, as can be seen in FIG.
[0065] The ceramic materials 6, 7 include ZnO. In particular, ZnO is the main component of the ceramic materials 6, 7. Furthermore, the ceramic materials 6, 7 may include varistor-forming oxides, such as bismuth oxide or rare earth oxides (e.g., praseodymium oxide), and other oxides that improve the varistor properties.
[0066] The ceramic materials 6 and 7 are chemically nearly identical. In particular, the ceramic materials 6 and 7 are chemically identical by more than 99%. However, the ceramic materials 6 and 7 have different dielectric constants ε0*ε r or relative dielectric constant ε r In particular, the dielectric constant ε0*ε of ceramic materials 6 and 7 r or relative dielectric constant ε r differ from each other by a factor of more than 5. In that case, the dielectric constant of the first ceramic material 6, and thus in the active region 3, is greater than the dielectric constant of the second ceramic material 7, and thus in the region 4 near the surface.
[0067] This is because ceramic materials 6 and 7 contain monovalent elements X + (where X + Li + , Na + , K + or Ag + This is achieved by differing from one another in the concentrations of
[0068] For example, ceramic materials have a maximum of 50 ppm < Δc(X +)<5000 ppm, where Δc denotes the maximum concentration difference occurring between the active region 3 and the near-surface region 4. Preferably, the concentration of monovalent elements in the near-surface region 4 is higher than in the active region 3 by 100 ppm to 1000 ppm.
[0069] Monovalent element Li + , Na + , K + , Ag + acts as "acceptor doping" in semiconducting ZnO. Therefore, the above-mentioned doping can be applied to all ZnO-based varistor ceramics (regardless of recipe).
[0070] In general, the ceramic materials 6, 7 must be doped with acceptors that have relatively low diffusion constants. Furthermore, the dopants that differentiate the ceramic materials 6, 7 must occur in low concentrations.
[0071] Concentration X in active area 3 + (The concentration of the monovalent element in the first ceramic material 6) is at a low level (X + <100 ppm). In other words, in the active area 3, + The concentration of is much lower than in the non-active areas or in the area 4 near the surface.
[0072] Monovalent element X + A low concentration of X is accompanied by a large (or relatively large) dielectric constant. Thus, the active region 3 has a higher dielectric constant / permittivity than the near-surface region 4. + As the concentration of Zn increases, the dielectric constant decreases. Overall, a significant decrease in the dielectric constant is achieved already when adding small amounts of monovalent elements.
[0073] In summary, the two ceramic materials 6 and 7 are composed of monovalent elements X +are combined such that the highest concentration is in the near-surface region 4 and the lowest concentration is in the active region 3. The second ceramic material 7 therefore functions as an insulating coating layer with acceptor doping and low dielectric constant. Starting from the near-surface region 4, the concentration gradually decreases (concentration gradient) in the direction of the active region 3. This significantly reduces the parasitic capacitance / stray capacitance of the multilayer varistor 1.
[0074] Since the ceramic materials 6, 7 are chemically nearly identical, sintering of the ceramic does not lead to mechanical (cracks, bending) and chemical (reaction zones, diffusion zones) problems.
[0075] Figure 2 shows a second embodiment of the multilayer varistor 1. Regarding the design and arrangement of the internal electrodes 5 and external electrodes 9, please refer to the explanations related to Figure 1.
[0076] In contrast to the multilayer varistor shown in FIG. 1, the multilayer varistor in this embodiment is a multilayer varistor having different concentrations of monovalent element X + The semiconductor device has three ceramic materials / varistor ceramics 6, 7, 8, including a first or primary ceramic material 6, which is arranged in the active area 3, as already explained in relation to FIG. 1. The second and third ceramic materials (modified ceramic materials) 7, 8 are arranged in the near-surface area 4. In that case, the third ceramic material 8 is arranged between the first and second ceramic materials 6, 7.
[0077] The first ceramic material 6 has a low concentration of monovalent elements. Thus, the first ceramic material 6 has a high dielectric constant. The second ceramic material 7 has a higher concentration of monovalent elements than the first ceramic material 6. The concentration of monovalent elements in the third ceramic material 8 is between the first ceramic material 6 and the second ceramic material 7. In particular, the first ceramic material 6 has the lowest concentration of monovalent elements and the second ceramic material 7 has the highest concentration of monovalent elements. The third ceramic material 8 has a medium concentration. Thereby, a concentration gradient is generated.
[0078] In that case, the concentration of acceptors in the second and third ceramic materials 7, 8 is for example 50 ppm to 5000 ppm higher than in the active ceramic layer (first or primary ceramic material 6). The second and third ceramic materials 7, 8 act as insulating coating layers or insulating zones with acceptor doping and low dielectric constant.
[0079] Figure 3 shows a third embodiment of the multilayer varistor 1. With regard to the design and arrangement of the external electrodes 9, reference is made to the explanation in relation to figure 1. In contrast to the embodiment shown in figures 1 and 2, the internal electrodes 5 in this example are arranged tip-to-tip (Spitze-zu-Spitze-Lage). The area between the tips of the internal electrodes 5 forms the active area 3 of the multilayer varistor 1. In addition, the multilayer varistor 1 has a metallic shielding or Faraday electrode 10, which enhances the protection of the multilayer varistor 1 against electrostatic discharges.
[0080] Similar to the multilayer varistor described in relation to FIG. 2, the multilayer varistor 1 in this embodiment has different concentrations of the monovalent element X + The ceramic material has three components 6, 7, and 8, including:
[0081] The Faraday electrode 10 contributes to preventing diffusion between the ceramic materials 6, 7, 8. Due to the reduced diffusion, a defined concentration gradient results and, therefore, a defined gradient of the electrical properties, in particular of the dielectric constant. The thickness of the covering layers (second and third ceramic materials 7, 8) is selected in such a way that the diffusion of acceptors into the active area 3 is as little as possible. The thickness of the covering layer is understood to be the extent of the second ceramic material 7 or the third ceramic material 8, respectively, perpendicular to the main extension direction of the multilayer varistor 1.
[0082] Overall, the concentration of acceptors in the second and third ceramic materials 7, 8 is 50 ppm to 5000 ppm (preferably 100 ppm to 1000 ppm) higher than in the active ceramic layer (first ceramic material 6). The second and third ceramic materials 7, 8 function as acceptor doping and insulating coating layers with low dielectric constant. For further design features of the ceramic materials 6, 7, 8, see the description of FIG. 2.
[0083] A particular advantage of this invention is that the modified varistor ceramic 7, 8 (second or third ceramic material 7, 8) and the original varistor ceramic (first or primary ceramic material 6) are not significantly different from each other chemically, but their electrical properties are significantly different, so the materials are otherwise nearly identical and can be processed without problems.
[0084] In the following, a method for manufacturing a multilayer varistor 1, in particular a multilayer varistor according to the above embodiment, is described. The method comprises the following steps:
[0085] A) In a first step, ceramic powders of individual components are prepared. In this case, a first ceramic powder is prepared to form a first ceramic material (primary ceramic material) 6. A second ceramic powder is prepared to form a second ceramic material (modified ceramic material) 7. In one embodiment, a third ceramic powder can also be prepared to form a third ceramic material (modified ceramic material) 8 (see figures 2 and 3). The ceramic powders are chemically more than 99% identical. The ceramic powders essentially comprise ZnO as a base material. Table 1 shows possible compositions of the base material of the ceramic powder. Of course, other compositions are also possible, in which ZnO is the main component of the ceramic material.
[0086] [Table 1]
[0087] However, ceramic powders do not contain monovalent elements X + In particular, ceramic powders differ in concentration X + 50ppm≦Δc(X + )≦5000 ppm.
[0088] In that case, the first or primary ceramic powder has a minimum concentration of acceptor / monovalent element. Preferably, the monovalent element X in the first ceramic powder + is <100 ppm. The second ceramic powder has a maximum concentration of acceptor / monovalent elements. The third ceramic powder has a moderate / intermediate concentration of acceptor / monovalent elements.
[0089] In a second step B), the formation of green sheets from the ceramic powder takes place. For this, the powder is first ground, spray dried and decarburized. The decarburized powder is slurried with organic binders and dispersants and subsequently rolled into green sheets. The sheets are cut to the appropriate shape.
[0090] In a further step C), a partial printing of a metal paste (preferably silver and / or palladium) is performed on parts of the green sheets in order to form internal electrodes 5. In that case, only those green sheets which will later be arranged in the active areas 3 are partially printed with the metal paste, in other words only those green sheets which are produced from the first ceramic powder are printed with the metal paste.
[0091] Optionally, another metal paste (preferably silver and / or palladium) can be printed onto a portion of the green sheet (see FIG. 3) to form a shield electrode 10. Preferably, this metal paste is printed onto the green sheet having minimal and / or moderate concentrations of monovalent elements (FIG. 3).
[0092] In a further step D) a stack of printed and unprinted green sheets is carried out, the stack being such that the final multilayer varistor 1 is composed of monovalent elements X + , which decreases starting from the second ceramic material 7 through the third ceramic material 8 (FIGS. 2 and 3) to the first ceramic material 6.
[0093] In further steps the green sheets are laminated, decarburized and sintered, the sintering temperature then being preferably 1100° C.
[0094] In a final step the application of the external electrodes 9 takes place.
[0095] The method produces a multilayer varistor 1 having very low stray capacitance and therefore low capacitance.
[0096] The advantage of the invention is that the production involves very little effort. The modified varistor ceramic (second or third ceramic material 7, 8) is treated in the production exactly the same as the original / primary varistor ceramic (first ceramic material 6), since these materials differ only slightly chemically. The powder, slurry and sheet properties of the materials are therefore very similar and can be processed in the same way. The same applies to the processing of the foil into stacks and the finishing of the parts (cutting, decarburization, sintering). The elements that distinguish the materials from one another, for example potassium, have only small concentration differences (concentration gradients), so that their diffusion into the active area can be neglected even during sintering. The covering layer can therefore be dimensioned with a sufficiently large thickness, which enhances the shielding effect.
[0097] For the characterization of the coating layers, starting from the substrate (see Table 1), modifications (variations with different doping according to Table 2 below) were carried out and their dielectric constants were measured using the test method described above. For this purpose, the powder mixtures were respectively ground, evaporated and decarburized. The decarburized powders were granulated with an organic binder and pressed into disks (diameter 15 mm, height 1 mm). The disks were sintered and ground to a height of 0.3 mm. Finally, the disks were printed on both sides with silver paste in the form of circles (diameter 5 mm) and baked.
[0098] The capacitance of the disk was measured at 1 V and 1 kHz (see Table 2). With the formula for the capacitance of a plate capacitor, the dielectric constant or relative permittivity of the ceramic could be determined: ε r =(C*d) / (A*ε0).
[0099] [Table 2]
[0100] A characterization test method was used to prepare possible compositions having reduced dielectric constants suitable for testing the present invention in multilayer varistors.
[0101] Finally, the present study is briefly summarized below.
[0102] Three ceramic powders were produced which differed only in the potassium and lanthanum content in the ppm range (see Table 2). The main component of all powders was zinc oxide (see Table 1).
[0103] The first ceramic powder matched in composition the substrate (see Table 1). The second ceramic powder was additionally doped with 1000 ppm potassium. The third ceramic powder was additionally doped with 1000 ppm potassium and 1000 ppm lanthanum.
[0104] The powder mixture thus produced was milled, spray dried and decarburized. The decarburized powder was slurried with organic binders and dispersants and rolled into sheets. The sheets were trimmed to the appropriate shape, printed with palladium paste, laminated and cut into multi-layer parts.
[0105] For the test, two internal electrodes (120 micron electrode spacing and 0.8 mm 2 The simplest design (see Figure 1) of a 1206 ML-varistor with an overlap area of 0.01 mm was chosen. Three different parts were manufactured using three different ceramic sheets.
[0106] The first type of components consisted consistently of a substrate (=reference type). The second type of components consisted essentially of a substrate with a coating layer made of a second ceramic (with an increased potassium concentration). The third type of components consisted essentially of a substrate with a coating layer made of a third ceramic (with an increased potassium concentration, doped with lanthanum).
[0107] The components thus produced were each sintered at 1100°C, whereupon a polished pattern showed that the coating layer was sintered together with the core layer without defects (no cracks, etc.) Finally, the components were metallized with external electrodes consisting of silver layers and fired.
[0108] The capacitance of the components was measured at 1 V and 1 MHz. The first type of component (reference type) had a capacitance of 17.7 ± 3.1 pF. The second type of component (layer with increased potassium concentration) had a capacitance of 13.2 ± 1.3 pF. This corresponds to a capacitance reduction of 25%. The third type of component (layer with increased potassium concentration and doped with lanthanum) had a capacitance of 11.1 ± 2.4 pF. This corresponds to a capacitance reduction of 37%. It could therefore be shown that the simplest method of application of the invention already leads to a significant reduction in the total capacitance of the multilayer varistor.
[0109] The current / voltage characteristic curves of the components were measured with increasing static currents in the range from 10 nA to 1 mA. The varistor voltage at 1 mA for the first type of component (reference type) was 2159 ± 144 Vmm -1 The varistor voltage at 1mA for the second type of component was 2210±172Vmm -1 This corresponds to a change in the varistor voltage of only 2%. The varistor voltage at 1mA for the third type of component was 2273±183Vmm. -1 This corresponds to a 5% change in the varistor voltage.
[0110] That is, the varistor voltage (U v It is clear that the current draw (@1mA) is hardly affected by the use of the coating layer / modified varistor ceramic. From this it can be concluded that the active volume of the varistor is not affected or even damaged by the coating layer.
[0111] The description of the subject matter presented herein is not limited to individual specific embodiments, but rather the features of the individual embodiments can be combined with each other in any combination, insofar as this is technically meaningful. [Explanation of symbols]
[0112] 1 Multilayer Varistor 1a Top surface 1b Bottom side 2 Ceramic body 3. Active Area 4. Near-surface region 5 Internal electrode 6. First Ceramic Material 7. Second Ceramic Material 8. The third ceramic material 9 External electrode 10 Protective electrode
Claims
1. A method for manufacturing a multilayer varistor (1) comprising the following steps: A) providing a first ceramic powder for producing a first ceramic material (6) forming an internal region having an active area (3) and at least one second ceramic powder for producing a second ceramic material (7) forming a near-surface region (4), the second ceramic powder being composed of a monovalent element X + =(Li + , Na + , K + or Ag + a maximum molar concentration difference Δc between the active region (3) where the minimum molar concentration exists and the surface-near region (4) where the maximum molar concentration exists is in the range of 50 ppm≦Δc(X+)≦5000 ppm, and the main component of the first ceramic material (6) and the second ceramic material (7) is zinc oxide (ZnO); B) slurrying the ceramic powder to form a green sheet; C) partially printing a metal paste on a portion of the green sheet to form an internal electrode (5); D) stacking the printed and unprinted green sheets such that the first ceramic material (6) forms the interior region, the internal electrodes (5) are formed within the interior region, and the second ceramic material (7) forms the near-surface region (4); E) laminating, decarburizing and sintering the green sheets; F) Applying the external electrodes (10).
2. In step C), the monovalent element X is added to the green sheet rather than to the other green sheets. + The method of claim 1 , wherein the green sheet having a low molar concentration of is partially printed with a metal paste.
3. 3. The method according to claim 1 or 2, wherein the green sheets are stacked in step D) such that the second ceramic material (7) forms a covering layer of the multilayer varistor (1).
4. The method according to any one of claims 1 to 3, wherein the ceramic powder comprises ZnO as a main component.
5. The method according to any one of the preceding claims, wherein the ceramic material (6, 7) comprises a varistor-forming oxide or a rare earth oxide and another oxide improving the varistor properties.
6. The method according to any one of the preceding claims, wherein the ceramic material (6, 7) is additionally doped with Pr, La or Y.
7. The method according to any one of the preceding claims, wherein the ceramic materials (6, 7) have different potassium and lanthanum contents.
8. The method according to any one of the preceding claims, wherein the second ceramic material (7) located in the near-surface region (4) is doped with 1000 ppm of potassium.
9. 9. The method according to claim 8, wherein the second ceramic material (7) is additionally doped with 1000 ppm La.
10. 10. The method according to claim 8 or 9, wherein the second ceramic material (7) doped with lanthanum has a reduced stray capacitance compared to the second ceramic material (7) doped only with potassium.
11. The first ceramic material (6) is a monovalent element X + and said second ceramic material (7) has a minimum molar concentration of monovalent element X + The method according to any one of claims 1 to 10, wherein the maximal molar concentration is
12. In step A), a third ceramic powder for producing a third ceramic material (8) is prepared, and the monovalent element X in the third ceramic powder is + The method according to any one of claims 1 to 11, wherein the molar concentration of is less than in the second ceramic powder but greater than in the first ceramic powder.
13. In step D), the green sheet is + The method according to any one of claims 1 to 12, wherein the first ceramic material (6) and the second ceramic material (7) are stacked to have a defined molar concentration gradient of 0.01 to 0.15, the molar concentration decreasing from the second ceramic material (7) to the first ceramic material (6).
14. A multilayer varistor (1), 1. A multilayer varistor (1), comprising a ceramic body (2) having a number of internal electrodes (5), an internal region and a surface-nearby region (4) having an active region (3), at least one first ceramic material (6) and at least one second ceramic material (7), the main components of the first ceramic material (6) and the second ceramic material (7) being zinc oxide (ZnO), the first ceramic material (6) being formed in the internal region and the second ceramic material (7) being formed in the surface-nearby region (4), the number of internal electrodes (5) being formed in the internal region, and a maximum molar concentration difference Δc occurring between the active region (3) having the lowest molar concentration and the surface-nearby region (4) having the highest molar concentration with respect to the molar concentration of a monovalent element X+=(Li+, Na+, K+ or Ag+) is in the range of 50 ppm≦Δc(X+)≦5000 ppm.
15. 15. The multilayer varistor (1) according to claim 14, wherein the first ceramic material (6) is arranged on the active area (3) and the second ceramic material (7) forms an insulating coating layer of the ceramic body (2).
16. Multilayer varistor (1) according to claim 14 or 15, wherein the ceramic material (6, 7) comprises a varistor-forming oxide or rare earth oxide and another oxide improving the varistor properties.
17. 17. A multilayer varistor (1) according to claim 16, wherein the ceramic material (6, 7) is additionally doped with Pr, La or Y.
18. A multilayer varistor (1) according to any one of claims 14 to 17, wherein the second ceramic material (7) is doped with 1000 ppm of potassium.
19. 19. A multilayer varistor (1) according to claim 18, wherein the second ceramic material (7) is additionally doped with 1000 ppm La.
20. 20. A multilayer varistor (1) according to claim 18 or 19, wherein the second ceramic material (7) doped with lanthanum has a reduced stray capacitance compared to the second ceramic material (7) doped only with potassium.
21. The multilayer varistor (1) according to any one of claims 14 to 20, wherein the ceramic body (2) comprises at least three ceramic materials (6, 7, 8), a third ceramic material (8) being arranged between the first ceramic material (6) and the second ceramic material (7).
22. Monovalent element X + The highest molar concentration of the monovalent element X is present in the region (4) near the surface. + A multilayer varistor (1) according to any one of claims 14 to 21, wherein a minimum molar concentration of is present in the active area (3).
23. The first ceramic material (6) is a monovalent element X + and said second ceramic material (7) has a minimum molar concentration of monovalent element X + A multilayer varistor (1) according to any one of claims 14 to 22, having a maximum molar concentration of
24. The third ceramic material (8) is a monovalent element X + A multilayer varistor (1) according to claim 23, which is dependent on claim 21, having a medium concentration of
25. A multilayer varistor (1) according to any one of claims 14 to 24, wherein the chemical composition of each of the ceramic materials (6, 7, 8) differs from each other by no more than 1%.
26. A multilayer varistor (1) according to any one of claims 14 to 25, wherein the relative dielectric constants εr of the first and second ceramic materials (6, 7) differ from each other by a factor of 5 or more.
27. 22. A multilayer varistor (1) according to claim 21, wherein the dielectric constants εr of the second ceramic material (7) and the third ceramic material (8) are smaller than the dielectric constant εr of the first ceramic material (6).
28. The monovalent element X in the active region (3) + A multilayer varistor (1) according to any one of claims 14 to 27, wherein the molar concentration of is less than 100 ppm.
29. Monovalent element X + A multilayer varistor (1) according to any one of claims 14 to 28, wherein the molar concentration of gradually decreases starting from the near-surface region (4) towards the active region (3).
30. Multilayer varistor (1) according to any one of claims 14 to 29, wherein the thickness of the second and / or third ceramic material (7, 8) is adapted to the diffusion behaviour of the monovalent element.
31. A multilayer varistor (1) according to any one of claims 14 to 30, wherein the ceramic material (6, 7, 8) is based on ZnO.
Citation Information
Patent Citations
ceramic material, ceramic component with the ceramic material and use of the ceramic component
DE10026258A1
Varistor component with increased surge current absorption capacity
DE102017105673A1
Multilayer varistor with field-optimized microstructure and module featuring the multilayer varistor
DE102018116221A1
Laminated voltage nonlinear resistor
JP1985057905A
Low-capacitance chip varistor and its manufacture
JP1999003809A